Rethinking community from Peru : the political philosophy of José María Arguedas - Feldman, Irina Alexandra (Illuminations (Pittsburgh, Pa.), 2014)
"Peruvian novelist, poet, and anthropologist Jose María Arguedas (1911-1969) was a highly conflicted figure. As a mestizo, both European and Quechua blood ran through his veins and into his cosmology and writing. Arguedas's Marxist influences and ethnographic work placed him in direct contact with the subalterns he would champion in his stories. His exposes of the conflicts between Indians and creoles, and workers and elites were severely criticized by his contemporaries, who sought homogeneity in the nation-building project of Peru. In Rethinking Community from Peru, Irina Alexandra Feldman examines the deep political connotations and current relevance of Arguedas's fiction to the Andean region. Looking principally to his most ambitious and controversial work, All the Bloods, Feldman analyzes Arguedas's conceptions of community, political subjectivity, sovereignty, juridical norm, popular actions, and revolutionary change. She deconstructs his particular use of language, a mix of Quechua and Spanish, as a vehicle to express the political dualities in the Andes. As Feldman shows, Arguedas's characters become ideological speakers and the narrator's voice is often absent, allowing for multiple viewpoints and a powerful realism. Feldman examines Arguedas's other novels to augment her theorizations, and grounds her analysis in a dialogue with political philosophers Walter Benjamin, Jean-Luc Nancy, Carl Schmitt, Jacques Derrida, Ernesto Laclau, and Álvaro García-Linera, among others. In the current political climate, Feldman views the promise of Arguedas's vision in light of Evo Morales's election and the Bolivian plurality project recognizing indigenous autonomy. She juxtaposes the Bolivian situation with that of Peru, where comparatively limited progress has been made towards constitutional recognition of the indigenous groups. As Feldman demonstrates, the prophetic relevance of Arguedas's constructs lie in their recognition of the sovereignty of all ethnic groups and their coexistence in the modern democratic nation-state, in a system of heterogeneity through autonomy--not homogeneity through suppression. Tragically for Arguedas, it was a philosophy he could not reconcile with the politics of his day, or from his position within Peruvian society"--
Keywords: Arguedas, Jose María : Criticism and interpretation; Arguedas, Jose María : Political and social views; Arguedas, Jose María : Todas las sangres; Indians of South America : Andes Region : Politics and government; Sovereignty in literature; Community life in literature; Social conflict in literature; Ethnic relations in literature; Peruvian fiction : 20th century : History and criticism; Andes Region : Politics and government